2, 4-Diamino-5-(phenylthio)-5H-chromeno [2, 3-b] pyridine-3-carbonitriles as green and effective corrosion inhibitors: gravimetric, electrochemical, surface morphology and theoretical studies. Issue 59 (3rd June 2016) - Verma, Chandrabhan; Olasunkanmi, Lukman O.; Obot, I. B.; Ebenso, Eno E.; Quraishi, M. A.
Abstract : The inhibition of mild steel corrosion in 1 M HCl by three newly synthesized 2, 4-diamino-5-(phenylthio)-5 H -chromeno[2, 3- b ]pyridine-3-carbonitriles was studied using the weight loss method, electrochemical techniques, surface morphology studies and theoretical methods. Abstract : The inhibition of mild steel corrosion in 1 M HCl by three newly synthesized 2, 4-diamino-5-(phenylthio)-5 H -chromeno[2, 3- b ]pyridine-3-carbonitriles (DHPCs) namely, 2, 4-diamino-7-nitro-5-(phenylthio)-5 H -chromeno[2, 3- b ]pyridine-3-carbonitrile (DHPC-1), 2, 4-diamino-5-(phenylthio)-5H-chromeno[2, 3- b ]pyridine-3-carbonitrile (DHPC-2) and 2, 4-diamino-7-hydroxy-5-(phenylthio)-5 H -chromeno[2, 3- b ]pyridine-3-carbonitrile (DHPC-3) was studied using weight loss method, electrochemical techniques, surface morphology (SEM, AFM) studies and theoretical (quantum chemical calculations and molecular dynamic simulation) methods. The weight loss and electrochemical measurements showed that the inhibition efficiency increases with increasing inhibitor concentration and the relative trend of inhibition performance is DHPC-3 > DHPC-2 > DHPC-1. A potentiodynamic polarization study reveals that the investigated DHPCs act as mixed type inhibitors. The adsorption of the DHPCs on the mild steel surface obeys the Langmuir adsorption isotherm and involves both physisorption and chemisorption modes. The presence of the electron releasing –OH group at position seven on the chromenopyridine ring is considered to be responsible for the highest inhibition efficiency of DHPC-3 among the studied compounds. Whereas the presence of the electron withdrawing nitro (–NO2 ) group at position seven on the chromenopyridine ring is responsible for the lowest inhibitive strength of DHPC-1. Quantum chemical calculations and molecular dynamic simulation studies were undertaken to provide mechanistic insight into the roles of the different substituents (–OH and –NO2 ) on the corrosion inhibition behavior of the studied inhibitors.